Actuación de las cooperativas en el contexto del modelo de desarrollo productivo. Caso Innolac. - Cayapa Ikiam, Gilma Ibelia (2023)
: Productive development today is subject to situations of constant change, in which innovation deserves special attention in SMEs or organizations; the economic situation limits the performance with own capital so that to start a business one is requiered to resort to a bank loan, acting directly the cooperatives as a financial entity to support investment in a community, which promotes the development of this sector being part of the productive chain, ehere all participanta benefit. This investigation aims to determine the influence of the perfomance of cooperatives and their contribution to productive development. The “Innolac” case in the San Juan parish of the Chimborazo community is a descriptive investigation, using the hypothetical-deductive method with a non-experimental design. The survey was used as an instrument for data collection, structured with 23 questions; applied to the 12 partners of the Ñukanchik Ñan organization of the company “Innolac”. Based on the results, it is inferred that the company “Innolac” needs the perfomance of various cooperatives oriented to productive development that allow interaction with the community and promote productivity and sustained development, so a proposal is proposed whit various strategies, detailing the activities to be carried out in each of them to strengthen the marketing of cheese that the company offers and have better profitability and business stability.